Axial compressive behavior of circular concrete-filled steel tube stub columns with steel slag coarse aggregate. (May 2023) - Lu, Linhan; Zhang, Tianhe; Liang, Tao; Ren, Qingxin
Abstract: Steel slag, an industrial waste by-product, has been used as an alternative sustainable aggregate material in construction applications to attempt to manage solid waste. In this context, this work conducts axial compression tests on 5 groups of 10 circular steel slag concrete-filled steel tube (SSCFST) stub columns to study the feasibility of using steel slag coarse aggregate in concrete-filled steel tubes. The failure mode, load–strain curve, axial bearing capacity, initial axial stiffness, critical strain, and lateral deformation coefficient of the columns are analyzed. Further, the effects of the steel slag replacement ratio and cross-section dimension on the axial compressive properties of the specimens are quantified. These test results are employed to verify the reliability of a finite element model of the circular SSCFST stub columns established using Abaqus software. Then, a parametric analysis is performed to investigate the factors influencing the axial compressive performance of circular SSCFST stub columns. Moreover, the prediction accuracy of the existing design methods for the axial bearing capacity of circular SSCFST stub columns is evaluated. The results show that the replacement ratio of steel slag influences the axial compressive properties of concrete-filled steel tubes negligibly: the axial bearing capacity and initial axial stiffness of the columns decrease only by 1.4% and 2.4% respectively, at a steel slag replacement ratio of 100%. Increasing the cross-section diameter from 160 mm to 180 and 200 mm improves the axial bearing capacity of the columns by 25.6% and 54.6% respectively and reduces the critical strain by 12.4% and 21.7% respectively. The confinement factor is still critical to affecting the axial compressive performance of circular SSCFST stub columns. Finally, the formulas proposed in standards GB 50936–2014 and AIJ-2008 can be employed to calculate the axial bearing capacity of SSCFST stub columns.